Pharmaceutical development of co-crystals - Venczel Márta (2012)
Co-crystals are solids that are crystalline materials composed of two or more molecules in the same crystal lattice. Formation of co-crystals can solve several pharmaceutical issues raised during preformulation and formulation development e.g. by solubility, dissolution, bioavailability, chemical stability, decreasing hygroscopicity modulation. Formation of co-crystals could be a new path to improve physico-chemical and biopharmaceutical properties of medicines. One of the most difficult pharmaceutical formulation tasks is to improve the absorption of a weak base with poor and pH-dependent solubility properties; however, some combined chemical and formulation approaches give the possibility to reach this goal. Usually applied chemical tools are the salt and/or co-crystal formation, while the pharmaceutical approaches are micronization, nanonization, and elaboration of lipidic and amorphous formulations. However, to reach the targeted pharmacokinetic/pharmacodynamic (PK/PD) profiles, synergies of different chemical and pharmaceutical tools are needed.